Titillating the appetite of prawns - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A new technique is being developed in Israel that should increase the growth rates of freshwater prawns, as well as reducing food wastage. Prawns locate food by detecting compounds given off by food materials and when these compounds are no longer...